Markers of cell division cycle in glioblastoma: significance in prediction of treatment response and patient prognosis. (December 2013) - Yousaf, J.; Hills, C.; Dixit, S.; Achawal, S.; O'Brien, D.; Greenman, J.; Scott, I. S.
Abstract Objective. To investigate whether expression of regulatory components of the cell division cycle can be used independently to predict survival and response to adjuvant therapy in glioblastomas. Method. A tissue micro-array, constructed using glioblastomas (n = 66), was stained using antibodies against minichromosome maintenance protein-2 (Mcm-2), expressed throughout the cell-division cycle; geminin, a protein that prevents re-initiation of DNA replication; and cyclin A, an S-phase cyclin. A semi-quantitative labelling index (LI) was calculated using an average of 18 high-power fields (hpf) in three replicate cores. The patients were divided into two groups: Group 1 (n = 50) underwent surgery and radiotherapy with 24 patients receiving temozolomide, and Group 2 (n = 16) received surgical treatment only. Results. The LIs (median +/− IQR) for Group 1 were as follows: Mcm-2, 36.7% (22.9%–51.8%); geminin, 7.8% (5.8%–10.5%); and cyclin A, 4.2% (2.4%–6.9%). Elevated LIs, higher than the median, for geminin and cyclin A correlated with prolonged survival when the tumours received adjuvant therapy (Kaplan–Meier curves, p = 0.0046 and p = 0.0063 for geminin and cyclin A, respectively). Linear regression analysis revealed positive correlations with survival for Mcm-2 (p = 0.0376), geminin (p = 0.0006) and cyclin A (p = 0.004). In Group 2, there was no relationship between the patient survival and the LI for any marker. Conclusions. Geminin and cyclin A, each show potential as independent prognostic markers in glioblastomas receiving adjuvant therapy. This may reflect the fact that both geminin and cyclin A estimate proliferating tumour cell subpopulations sensitive to radio/chemotherapy. These markers could provide valuable prognostic information, even in small biopsies, especially if combined with O6MGMT expression and 1p;19q deletion status.